Teori Belajar Behavioristik Dalam Pembelajaran - ., P. Indra Murthi Suputra (Jurnal Pendidikan, Sains Dan Teknologi, 2023)
Behavioristic learning theory is a learning theory that focuses on changes in behavior that produce stimulus and response. In other words, learning is a form of behavior change with the interaction between stimulus and response. According to Thronedike, learning is a process of interaction between stimulus and response, it is clear that changes in behavior can be tangible or concrete, and non-concrete (cannot be observed). And according to Skinner, the relationship between stimulus and response occurs because through interaction with the environment it causes changes in behavior. behavior. Thus, this behavioristic communication theory focuses more on improving individual behavior for the better.